Identifying and Overcoming Barriers for Implementing Watson's Human Caring Science. (July 2019) - Pashaeypoor, Shahrzad; Baumann, Steven L.; Sadat Hoseini, Akram; Cheraghi, Mohammad Ali; Chenari, Hadi Ahmadi
The purposes of this paper are to identify and explore ways to overcome barriers to the implementation of Watson's human caring science in Iran. A literature search was done of PubMed, Elsevier, Science Direct, Ovid, ProQuest, Web of science, and Google Scholar between 1991 and 2018 using the search terms Watson's theory, clinical nursing, nursing theory, barriers to using theory, and carative factors or processes, separately and in combination. Organizational-level, practitioner-level, and educational barriers were found, and solutions for each are explored.